Seclusion and mechanical restraint in the wake of the COVID-19 pandemic: an increased use in mental health settings - Goulet, Marie-Hélène; Cassivi, Christine; Hupé, Catherine; Jean-Baptiste, Francelyne; Dumais, Alexandre (Frontiers in Psychiatry, 2024)
Purpose: COVID-19 pandemic-related restrictions have significantly changed the environment and the delivery of direct care in all health services, including psychiatric hospitals. The aim of the study is two-fold: 1) to retrospectively assess the incidence of seclusion and mechanical restraint in a Quebec mental health hospital over 4 years; and 2) to assess the impact of the COVID-19 pandemic on their incidence. Methods: We conducted a retrospective study based on medical records from a Quebec mental health hospital collected (a) from April 2016 to March 2019), (b) from April 2019 to March 2020 (pre-COVID onset), and (c) from April 2020 to March 2021 (post-COVID onset). Descriptive statistics, chi square tests, Mann-Kendall test and Welch's t-test were performed. Results: Following several years during which the use of restrictive measures remained stable, we have noted a significant increase within the first year following the COVID-19 pandemic. This increase can be seen in the use of both seclusion and restraints, which have risen 205% and 170% respectively. Conclusion: There are a multitude of factors associated with the incidence of seclusion and restraint that have the potential to be triggered during emergencies and global crisis situations, impacting in turn the rights of an already vulnerable population.